Proceedings of the X Iberoamerican Conference on Applications and Usability of Interactive TV jAUTI2021 - Abásolo Guerrero, María José (2022)
The X Ibero-American Conference on Applications and Usability of TVDI jAUTI 2021 is an organization of the Department of Electricity, Electronics and Telecommunications and the WiCOM-Energy Research Group of the University of the Armed Forces ESPE together with RedAUTI (Thematic Network on Applications and Usability of Interactive Digital Television). This year's edition was held from December 2 to 3, 2021 in the city of Sangolquí, Ecuador, taking place online. This book brings together 18 works presented on the design, development and experiences of applications for interactive digital television and related technologies (IPTV, Smart TV, Connected TV, and Web TV).